Effective and efficient design and manufacture of a plastic waste press machine - Prantasi Harmi Tjahjanti; A'rasy Fahruddin; Agus Hermawanto; Septian Firmansyah (Teknik Mesin - Sekolah Tinggi Teknologi Muhammadiyah Cileungsi, 2023)
In Madiredo Village, which is located in Pujon District, Malang Regency, there are many business programs. The problem is that these efforts result in a wide range of waste, including up to 5 tons per day of residential waste and other corporate waste. The debris was gathered from the Bengkaras Hamlet, Madirero Village Reduce, Reuse, Recycle (TPST 3R) Integrated debris Management Site. However, a lot of plastic garbage has still leaked out of the packing. The objective is to create a press machine (press) with an electric motor so that packed plastic trash and levers (used when the power goes out) no longer require manual work. The process involves designing and producing waste press machines, particularly for cardboard, plastic trash, and old bottles. Use of the 2016 version of Solidworks for the simulation design. The lowest stress, 2.038 x 104 N/m2, and the highest Von Misses stress, 2.825 x 108 N/m2, are determined by the modeling findings. The biggest displacement or deflection is 1.737 x 10 mm, while the smallest displacement is 0 mm. The values of the strain range from 1.880 x 10-7 to a minimum of 6.00 x 10-4. Safety factor has a value greater than 1 A 1 horsepower AC motor is used in the press machine's construction. Three different distance stopper pressing variables—33 cm, 35 cm, and 37 cm—as well as various types of waste plastic bags, plastic bottles, and cartons/cardboard are used to test the pressing performance. The results show that pressing plastic trash at a distance from the pressing stopper of 37 cm, a mass of 167 kg, a time of 2.2 minutes, and a compressive force of 6546.4 N/m2 may pack or package well for garbage in plastic bags